Revived Attention for Adult Craniopharyngioma - Mende, Klaus Christian; Pantel, Tobias Fabian; Flitsch, Jörg (Experimental and Clinical Endocrinology & Diabetes, 2020)
Craniopharyngioma as a rare tumor originating from cells of rathke’s pouch and representing 2–5% of all intracranial tumors is a rare and generally benign neoplasm of the central nervous system with two incidence peaks one in childhood and one after 40 years of age. Data on adult patients is scarce compared to childhood onset tumors, however the burden of disease caused by the tumors and related treatment options is significant. Clinical symptoms range from headaches, visual disability, cranial nerve affection or hypothalamic symptoms (e. g. morbid obesity) to endocrine disorders. Most symptoms are related to tumor mass effect. The current standard of diagnostics is the determination of serum hormone levels and contrast enhanced magnetic resonance imaging often resulting in surgical treatment which holds a key role in all treatment concepts and should follow a hypothalamus sparing path. Radiation therapy may prove beneficial as adjuvant therapeutic option or in recurrent tumor, especially papillary tumors may be targeted using BRAF-600 inhibitors, targeted therapies for adamantinomatous craniopharyngioma have not yet reached a stage of clinical testing. Although prognosis regarding overall survival is favorable, life expectancy may be reduced due to the tumor itself as well as due to treatment effects. An important aspect especially in the adult population is the reduction in quality of life which is comparable to primary malignant brain tumors and metastases, calling for individual patient specific treatment approaches.
Keywords: Hypopituitarism; Insufficiencies; Cancer; Craniopharyngioma; QoL